Nenamjerne povrede djece i adolescenata liječenih u službama hitne medicinske pomoći: studija presjeka: Nenamjerne povrede djece i adolescenata liječenih u službama hitne medicinske pomoći - Jović, Duška; Skela-Savič, Brigita; Petrović-Tepić, Snežana; Knežević, Darija; Tepić, Aleksandar; Burgić-Radmanović, Marija; Dobrovoljski, Daniela; Egeljić-Mihailović, Nataša (Scripta Medica, 2022)
Background/Aim: Unintentional injuries among children and adolescents have become a common issue in public health care. The study objective was to analyse the characteristics and identify predictors associated with unintentional injuries in children and adolescents treated in emergency medical services (EMS) in the Republic of Srpska, Bosnia and Herzegovina.Methods: A cross-section study with retrospective analysis of WebMedic e-database from 14 EMS, in the period between January 2018 and December 2020 was conducted. Research included patients with unintentional injuries, aged ≤ 19 years, of both sexes. For comparison between groups, Chi-squared and multivariate logistic regression were used in risk factor analysis. Results: A total of 1,856 cases, most injuries resulted from falls (46.7 %) and traffic injuries (26.9 %) were identified. Boys were significantly more affected by injuries than girls (p < 0.001). Falls were the major cause for reporting to EMS among age groups of children (0-9 years) and adolescents (10-14 years), whereas injuries in traffic were dominant in adolescents aged 15 to 19. The most common injuries were head injuries (35.7 %). Risk factors of unintentional injuries were age (p < 0.001), sex (p = 0.046), weekday (p = 0.016), winter (p = 0.014), body region (head, abdomen, lower and upper limbs (p < 0.001), thorax (p = 0.009)).  Conclusions: There were significant differences in characteristics of unintentional injuries according to age and sex. Chances for occurrence of unintentional injuries among children increased with their age, especially for boys. These differences might indicate areas where preventive measures should be undertaken.